Adverse selection in the annuity market with sequential and simultaneous insurance demand - Johann K. Brunner; Susanne Pech (Johannes Kepler University of Linz, Department of Economics, 2002)
This paper investigates the effect of adverse selection on the private annuity market in a model with two periods of retirement. In order to introduce the existence of limited-time pension insurance, we assume that for each period of retirement separate contracts can be purchased. Demand for the two periods can be decided either sequentially or simultaneously. We show that different risk-groups prefer different types of contracts, and that only the sequential contracts, which are favourable for the long-living individuals, represent an equilibrium.
Keywords: D82; D91; G22; 330; annuity markets; adverse selection; uncertain lifetimes; equilibrium; Private Rentenversicherung; Versicherungsökonomik; Altersgrenze; Adverse Selektion; Sterblichkeit; Risiko; Spieltheorie; Theorie